Application of remote accounting projects when teaching mathematics - Vitaly V. Bogun (Высшее образование в России)
The author presents the information dynamic system of monitoring the educational projects. It has been being applied for the organization of mathematics distance learning. The main features of this information system and the methodical aspects concerning its using at implementation of accounting projects while learning mathematics are considered.